Karakteristik Penduduk Miskin dan Penyebab Kemiskinan di Desa Sukagalih - Lisnawati Sopiah; Ria Haryatiningsih (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The research objective was to find out the characteristics and causes of poverty in Sukagalih Village. Sukagalih Village is an area with the highest poverty rate in Cikalongkulon District. Low access to health and clean water, dense slum areas, and low level of public education. This type of research is descriptive quantitative using primary data. The population in this study is the people of Sukagali Village. The research sample consisted of 90 respondents who were determined by the slovin formula with simple random sampling technique. Data collection methods were carried out by questionnaires, interviews, and documentation. The results of this study indicate that the causes of poverty in Dukagalih Village are low income, Sukagalih Village has poor characteristics, especially from the variables of income patterns, consumption expenditure and fulfillment of food needs. Meanwhile, from the health variable, the poor in Sukagalih Village are still able to meet standard health needs, namely they are still able to buy medicine and seek treatment at the puskesmas or midwife. For the residential housing variable, the poor residents of Sukagalih Village are still able to have their own houses with permanent buildings. Abstrak.T ujuan penelitian adalah untuk mengetahui bagaimana karakteristik penduduk miskin dan penyebab kemiskinan di Desa Sukagalih. Desa Sukagalih merupakan daerah dengan tingkat kemiskinan tertinggi di Kecamatan Cikalongkulon. Rendahnya aksesibilitas kesehatan dan air bersih, padatnya kawasan pemukiman kumuh, dan rendahnya tingkat pendidikan masyarakat. Jenis penelitian ini adalah deskriptif kuantitatif dengan menggunakan data primer. Populasi dalam penelitian ini adalah masyarakat Desa Sukagali. Sampel penelitian berjumlah 90 responden yang ditetapkan dengan rumus slovin dengan teknik simple random sampling. Metode pengumpulan data dilakukan dengan kuesioner, wawancara, dan dokumentazi.Hasil penelitian ini menunjukan faktor penyebab kemiskinan pada Desa Dukagalih adalah pendapatan rendah, Desa Sukagalih memiliki karakteristik miskin terutama dari variable pola pendapatan, pengeluaran konsumsi dan pemenuhan kebutuhan pangan. Sementara dari variabel kesehatan penduduk miskin Desa Sukagalih masih dapat memenuhi kebutuhan kesehatan yang standar yaitu masih mampu membeli obat dan berobat ke puskesmas atau bidan. Untuk variable perumahan penduduk, penduduk miskin Desa Sukagalih masih mampu memiliki rumah sendiri dengan bangunan yang bersifat permanen.